Effect of different NaCl Concentrations on Accumulation of Some Chemical Elements in Leaves and Roots of Sugar Beet ( Beta vulgaris L.) Seedling - , Baha Eldin M. Idris; Kauther S. Ali; Wael A. Marajan; Hatim A. Sulfab (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2020)
An experiment was conducted in pots at the demonstration farm of College of Agriculture, University of Bahri, Sudan during 2016-2017 to study the effect of different NaCl concentration on accumulation of Sodium (Na+), Calcium (Ca++) .Potassium ( K+), and Phosphorus (P) in leaves and roots of sugar beet seedling. The experiment was arranged in randomized complete block design (RCBD) with three replications and four treatments of different concentration of sodium chloride in soil. The treatments were 4 dS/m, 8 dS/m , 12 dS/m , and 16 dS/m referred to as S1, S2, S3, and S4 respectively. Results showed that when NaCl concentration increased in soil, Na+ accumulation significantly increased in sugar beet seedling leaves and roots. Ca++ accumulation in leaves significantly increased and not significantly in roots of sugar beet seedling when NaCl concentration was increased. Higher concentration of Nacl decreased significantly K+ accumulation in leaves and roots of sugar beet seedling. Increasing concentration of Nacl increased accumulation of P in sugar beet seedling leaves and root.